Interaction Between Surface and Underground Waters of the Itapemirim and Itabapoana River Basins in the Southern part of the State of Espírito Santo, Southeastern Brazil - Gonçalves, José Augusto Costa; Almeida, Milena Stefany Lage; Vieira, Eliane Maria; Paiva, Brenda Luiza Ferreira; Ferreira, Mariana Araújo Mendes; Marcellino, Lázaro Correa (Anuário do Instituto de Geociências, 2023)
Itapemirim River basin and part of the Itabapoana River basin are located in the southern area of the State of Espírito Santo, covering 26 municipalities. Knowledge of these basins’ hydrogeological characteristics provides information on the groundwater potential and the behavior of the river base flow during dry seasons. The objective of this study is to assess the relationship between surface and underground waters from the analysis of hydrograph units and information from tubular well logs. The Itabapoana River basin had the highest flow rates with mean specific capacity of 1415.1 m3 /h/m, while Itapemirim River basin wells yielded 0.6941 m3 /h/m. The percentage of underground discharge in relation to the total discharge exceeded 60% during all seasons in both basins.